Market Potential of Mobile Halal Poultry Slaughterhouses in Banten - Diqbal Satyanegara; Galih Ginanjar Saputra (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
This research explores the connection between students’ learning styles and their vocabulary achievement among second-grade learners. Utilizing a correlational research approach, the study gathered data through a questionnaire addressing visual, auditory, and kinesthetic learning preferences, along with a vocabulary achievement test. The participants included 25 students from Class C. Data were analyzed using the Pearson Product-Moment correlation method. The results show a strong positive relationship between each learning style and vocabulary achievement, with correlation values of r = 0.838 for visual, r = 1.000 for auditory, and r = 0.923 for kinesthetic styles. These findings suggest that students' preferred learning styles significantly impact their vocabulary acquisition. The study emphasizes the need for teachers to acknowledge and adapt to various learning styles in their teaching methods to support better vocabulary learning. It also recommends future studies with broader and more varied participant groups to allow for generalization and deeper exploration of causal links.